Edaphic factors influencing vegetation colonization and encroachment on arsenical gold mine tailings near Sudbury, Ontario. (September 2020) - Munford, Kimber E.; Watmough, Shaun A.; Rivest, Maxime; Poulain, Alexandre; Basiliko, Nathan; Mykytczuk, Nadia C.S.
Abstract: Mine tailings are found worldwide and can have significant impacts on ecosystem and human health. In this study, natural vegetation patterns on arsenical (As) gold (Au) mine tailings located in Sudbury, Ontario were assessed using transects located at the edge of the tailings and on the tailings. Vegetation communities were significantly different between the edge and open tailings areas of the site. Arsenic concentrations in both areas were extremely variable (from 285-17, 567 mg/kg) but were not significantly correlated with vegetation diversity at the site. Nutrients (carbon (C), phosphorus (P)) and organic matter concentrations were associated with higher diversity and with the presence of climax vegetation on the tailings, but there were no significant relationships between tailings chemistry and vegetation indices on the edge. Encroachment onto the tailings from the edge occurred in conventional succession patterns, with a clear gradient from grasses ( Agrostis gigantea ) to trees such as Picea glauca . On the tailings, a nucleation pattern was visible, distinct from conventional succession. Trees and shrubs such as Betula papyrifera and Diervilla lonicera were associated with higher diversity and higher nutrient concentrations in the underlying tailings, whereas grasses such as A. gigantea were not. We concluded that at all areas of the site, vegetation - particularly trees - was facilitating amelioration of the underlying tailings. Despite high concentrations of As, nutrients appeared to have a greater influence than metals on vegetation diversity. Graphical abstract: Image 1 Highlights: Nutrients (C, P) and OM were associated with higher diversity at the site. Pioneer vegetation species were encroaching from the forested edge, ameliorating soil. Singular colonizing plants were establishing in microsites on the open tailings. pH was associated with vegetation presence/absence on the open tailings. Abstract : Metal-tolerant pioneer vegetation, particularly trees and shrubs, were facilitating the establishment of less-tolerant climax vegetation on toxic, arsenical gold mine tailings.